Labour and Employment in Punjab - Kaur, Randeep (Journal of Commerce and Trade, 2012)
Productive employment generation with decent work conditions is an important concern not only for the national employment policy but also for the national agenda of inclusive growth .Although the overall economic growth achieved by the Indian economy, particularly during the current decade, has been impressive, employment growth has not kept pace. At a time, when India is aiming to achieve double-digit economic growth, commensurate employment growth assumes crucial importance from the point of view of sustaining overall high growth.